Impaired H-Reflex Adaptations Following Slope Walking in Individuals With Post-stroke Hemiparesis - Liang, Jing Nong; Lee, Yun-Ju; Akoopie, Eric; Kleven, Brooke Conway; Koch, Trisha; Ho, Kai-Yu (Frontiers in Physiology, 2019)
Background and Purpose: Short term adaptations in the Ia afferent-motoneuron pathway, as measured using the H-reflex, in response to altered ground reaction forces (GRFs) applied at the feet during slope walking have been observed in the non-impaired nervous system. The ability of the stroke-impaired nervous system to adapt to altered GRFs have not been examined. The purpose of this study was to examine the acute effects of altered propulsion and braking forces applied at the feet, which naturally occurs when walking on different slopes, on adaptations of the H-reflex pathway in individuals with chronic post-stroke hemiparesis. Methods: Twelve individuals chronically post-stroke and 10 age-similar non-neurologically impaired controls walked on an instrumented treadmill for 20 minutes under level, upslope and downslope conditions. GRFs were measured during walking and soleus H-reflexes were recorded prior to and immediately after walking. A 3 (limbs: paretic, non-paretic, and non-impaired) X 3 (slope: level, upslope, downslope) mixed factorial ANOVA was conducted on the propulsive and braking forces. A 2 (limb: paretic and non-impaired) X 2 (time: pre and post) X 3 (slope: level, upslope, and downslope) mixed factorial ANOVA was conducted to assess the soleus H-reflex amplitudes. Results: In both post-stroke and non-impaired groups, during downslope walking, peak propulsive forces decreased, while peak braking forces increased. In contrast, during upslope walking, peak propulsive forces increased and peak braking forces decreased. We observed reduced soleus H-reflex amplitudes immediately following 20 minutes of level, downslope and upslope walking in non-impaired individuals but not in the paretic legs of individuals with chronic post-stroke hemiparesis. Discussion and Conclusions: Similar pattern of change in peak propulsive and braking forces with respect to different slopes was observed in both individuals post-stroke and non-impaired individuals, but the magnitude of GRFs were smaller in individuals post-stroke due to the slower walking speed. Our results suggested that impaired modulation of the H-reflex pathway potentially underlies the lack of neuroadaptations in individuals with chronic post-stroke hemiparesis.